Simple light-emitting electrochemical cell using reduced graphene oxide and a ruthenium (II) complex - Tito, HAR (2017)
We report the use of conducting substrates from reduced graphene oxide (rGO) applied in light-emitting electrochemical cells (LECs) in which we used an electroluminescent polymer as a light-emitting layer. The emitting layer was composed of an organic metal complex of tris(2, 2′-bipyridine) ruthenium (II) linked to the sodium tetrafluoroborate anion ([Ru(bpy)3]+2)(BF4)−1. The luminance generated from the electroluminescent device was 6.89 Cd/m2 when applying a voltage of 13.48 V and a current of 10.19 mA. The luminance of this device was kept on almost constant for 36.84 min. The prolonged lifetime of the electrochemical device was achieved by depositing an rGO thin layer with a 161.3 nm thickness inside the LEC structure.